Fiqh al-Mu’āmalāt in Madrasah Aliyah Curriculum: Perspective of Islamic Economics, Entrepreneurship Education, and Islamic Financial Literacy - Liza, Fitri; Abdiguno, Panggih; Luhuringbudi, Teguh (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
This study explores the integration of Fiqh al-Mu’āmalāt into the Madrasah Aliyah curriculum through the lens of Islamic economic theory, entrepreneurship education, and Islamic financial literacy. The research aims to assess the effectiveness of the existing curriculum and identify areas for improvement. Data collection methods include questionnaires, interviews, and documentation, analyzed using data reconciliation, presentation, and construction approaches. The primary data source consists of 112 Madrasah Aliyah students from Bali and Jakarta. The findings reveal a discrepancy between students' awareness of the importance of Fiqh al-Mu’āmalāt (78.6% considered it useful) and its practical implementation in the curriculum, particularly in grades XI–XII. Analysis of the Grade X Fiqh textbooks indicates that while the content is comprehensive, it lacks applicability to real-world contexts. These findings suggest the need for curriculum restructuring to ensure the sustainable integration of Fiqh al-Mu’āmalāt. This study contributes to a comprehensive understanding of Fiqh al-Mu’āmalāt instruction by highlighting the relationship between theoretical knowledge and students' economic preparedness. However, its limitations include a restricted geographic scope and a focus on students' perceptions. Future research should incorporate cross-country longitudinal and comparative studies, as well as experimental research on effective Fiqh al-Mu’āmalāt teaching methodologies to enhance students’ practical financial and entrepreneurial competencies